"We don't have the same bodies; we don't react the same way": mothers and adolescent girls' perceptions of the risks and benefits of HPV vaccination in France. Issue 1 (31st December 2022) - Karafillakis, E; Peretti-Watel, P; Verger, P; Chantler, T; Larson, HJ
ABSTRACT: Human Papillomavirus (HPV) vaccination is one of the most publicly mistrusted vaccines in Europe, with countries such as France struggling with low vaccine uptake due to parental questioning of vaccine risks and benefits. However, limited evidence exists on adolescent girls' perceptions of the risks and benefits of HPV vaccination. The aim of this qualitative study was to provide an in-depth exploration and comparison of French mothers (n = 21) and adolescent girls' (n = 36) perceptions of the risks and benefits of HPV vaccination. A thematic analysis showed that adolescent girls and mothers perceived the risks and benefits of HPV vaccination differently, with girls reporting positive and beneficial views and emotions toward vaccination and mothers expressing concerns about possible risks. Adolescent girls also reported that both perceptions and actual risks and benefits may vary from one individual to another. Vaccine safety was also understood differently, with mothers reporting a widespread view that vaccines are unsafe and focusing on controversial side effects and girls discussing short-term consequences of vaccination (e.g. pain, fever) and administration and storage issues. Strategies to improve uptake of HPV vaccination should consider and address both the mothers' and daughters' perceptions and understandings of HPV vaccination.